India's new caste war: the archaeology of a perpetual conflict - Brij Mohan (2007)
Caste as a system of stratified inequality has globally survived in different forms since times immemorial. Its functionality on the subcontinent, however, is sustained by a mythologised social reality that runs contrary to the ideals of a secular democracy. This article seeks to theorise caste as a conceptual anomaly and a source of perenial strife - ascribed status, discontent and conflict - that pervade a civilisational crisis at the crossroads of progress. - Reproduced.
Keywords: Caste - India; Caste